Fundus autofluorescence imaging in hereditary ATTR amyloidosis with ocular involvement. (December 2013) - Veronese, Chiara; Marcheggiani, Eleonora B.; Tassi, Filippo; Gallelli, Ilaria; Armstrong, Grayson W.; Ciardella, Antonio P.
Abstract Fundus autofluorescence (AF) is a non-invasive technique for the evaluation of intrinsic autofluorescence of the tissues within the eye. In recent years, autofluorescence has become an important diagnostic tool for the assessment of various ocular diseases. A previous study has found that ex vivo Aβ amyloid plaques in the retina of a transgenic mouse model appear hyper-autofluorescent (hyper-AF) under specific wavelengths (excitation at 830 nm, emission at 630). We report the first description of hyper-AF ocular findings in a case of transthyretin-related familial amyloid polyneuropathy (FAP) associated with ocular involvement using AF imaging. A 47-year-old woman from Italy presented to our institution with a history of early onset FAP with ocular involvement due to the rare amyloidogenic transthyretin Glu54Lys mutation. AF imaging showed hyper-AF amyloid deposits associated with retinal vessels in both eyes and a hyper-AF amyloid deposit anterior to the optic disk in the right eye. Conclusion and Relevance: Further studies in FAP patients with different types of genetic mutations and various disease-stages are needed to better establish if non-invasive AF imaging is useful in detecting ocular amyloidosis.